From the margins to the center contemporary women and political communication - Sullivan, Patricia Ann; Turner, Lynn H. (Praeger, 1996)
Guinier, Clinton, and Reno have each adopted different strategies in confronting these boundaries and in challenging gender stereotypes, and their strategies dramatically illustrate the communication of contemporary political women. Of interest to all in speech communication, political science, and women's studies
Keywords: Frau; Communication in politics -- United States; Communication -- Sex differences; Women in public life -- United States; Women -- Language; Politische Rede; Rhetorik; USA